Calculation of the Required Power of Electric Motors for Overhead Crane Movement Mechanisms Using the Statistical Method - Kovalenko V.; Zhuravel O.; Strizhak V.; Iglin S.; Strizhak M. (Problems of the Regional Energetics, 2024)
The aim of this study is to determine the functional dependence for the calculation of the re-quired power of the electric motor of the traveling mechanism of the overhead traveling crane on the load capacity and span. The set aim is achieved by solving the following problems: figur-ing out how to calculate the power of the electric motor of the overhead traveling crane mecha-nism by the traditional methodology; selecting constants known from the initial data and varia-bles that require additional calculation; collecting and arranging statistical data - values of varia-bles for overhead cranes of different spans and load capacities; determining regression equa-tions based on statistical data - functions of two variables from the load capacity and span; sub-stituting the equations for the power of the overhead traveling crane mechanism from the load capacity and span. In the process of solving the set tasks, it was found that the greatest difficulty is the determination of static resistance and crane mass. Traditional calculation of these parame-ters requires the use of additional reference data and making design decisions of high responsi-bility. When searching for regression equations, the cubic model is-used, which provides high accuracy and does not overload the equation with summands. The most important result is the derivation of the final expression for determining the motor power as a function of two varia-bles - load capacity and span. The importance of the obtained results is that the proposed meth-od of calculation significantly reduces the time for the selection of the electric motor in the de-sign of a new crane, because there is no need to calculate or select additional parameters that are included in the traditional calculation. The proposed regularity is easier to integrate into comput-er-aided design systems. Since the calculation was based on statistical data of cranes manufac-tured and successfully operating, the probability of erroneous calculation is practically excluded.